The Social and Environmental effects of foreign Investment in Kosovo - Bajraktari, Halim; Rifat Hoxha; Agon Kokaj (European Journal of Multidisciplinary Studies, 2020)
The effects of different foreign companies that are expected to invest in Kosovo is a significant aspect of its effect in the environment. Pollution is an important factor that has become a major problem today. The geo-physical status of the country, situated in the central Balkans region, happens to be a corridor of economic change and prosperity. That prosperous positive upcoming change may be halted due to the continuous disruption of toxic and poisonous fumes being released into the atmosphere. Institutions are expected to undergo a real-time monitoring technique that will be able to allow certain factories to set up their headquarters and allow for production in law abiding rules and in full relation to the health environmental issue.